Constitutional justice from the perspective of the philosophy of Jeremy Waldron and the recent Venezuelan experience - Ghersi Rassi, Óscar (2018)
The article reviews Jeremy Waldron’s theory about the legitimacy and moral authority of the various forms of constitutional justice. According to this theory, it is always illegitimate insofar as it violates the principle of majority decision, the only moral principle of legitimate legal authority.The author explains the conditions that, according to Waldron, a political community must gather so that his theory is applicable. He also ventures into forwarding some criticisms to the author regarding these conditions.Specially, the problem of the regressivity of Waldron’s argument and the problem of stability of his conditions are explored. However, it is assumed that Waldron’s theory off ers important contributions and a reflection is made in the face of the Venezuelan constitutional reality. Finally, a theoretical outline is used to combine the institution of constitutional justice with the most relevant criticisms of Waldron.